1998
DOI: 10.1007/s002850050138
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific competition among macroparasites in a density-dependent host population

Abstract: Abstract. We analyze the dynamics of a community of macroparasite species that share the same host. Our work extends an earlier framework for a host species that would grow exponentially in the absence of parasitism, to one where an uninfected host population is regulated by factors other than parasites. The model consists of one differential equation for each parasite species and a single density-dependent nonlinear equation for the host. We assume that each parasite species has a negative binomial distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…It is clear that generalist parasites can overcome host density thresholds and drive a focal host species to extinction. The detailed community dynamics of multiple parasites sharing multiple hosts can be quite complex (Holt & Pickering 1985; Bowers & Turner 1997; Gatto & De Leo 1998; Bowers & Hodgkinson 2001; Holt et al. 2003).…”
Section: Theoretical Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is clear that generalist parasites can overcome host density thresholds and drive a focal host species to extinction. The detailed community dynamics of multiple parasites sharing multiple hosts can be quite complex (Holt & Pickering 1985; Bowers & Turner 1997; Gatto & De Leo 1998; Bowers & Hodgkinson 2001; Holt et al. 2003).…”
Section: Theoretical Mechanismsmentioning
confidence: 99%
“…It is clear that generalist parasites can overcome host density thresholds and drive a focal host species to extinction. The detailed community dynamics of multiple parasites sharing multiple hosts can be quite complex (Holt & Pickering 1985;Bowers & Turner 1997;Gatto & De Leo 1998;Bowers & Hodgkinson 2001;Holt et al 2003). However, multi-host parasites can clearly lead to apparent competition, where a host species drives a competitor to extinction by being more tolerant or encouraging reproduction of a parasite that harms its competitor (Schmitz & Nudds 1994;Holt et al 2003).…”
Section: Specialist Vs Generalist Parasites: Reservoirsmentioning
confidence: 99%
“…The conditions for coexistence or competitive exclusion in these multi-parasite models are basic to understand how a parasite community is structured (Janovy et al . 1990; Gatto and De Leo, 1998). Purely mathematical analysis have focused on general results that apply to all possible combinations of demographic parameters, whereas interspecific comparisons for both host and parasite species demonstrate that there are constraints on the combinations of parameter values observed in nature and this constraints are often related to body size (Peters, 1983; Skorping et al .…”
Section: Introductionmentioning
confidence: 99%
“…This in turn will affect the ability of further parasite species to establish in an already infected host. In addition, optimal parasite body size was derived by Morand and Poulin (2002) as that maximizing the reproductive number R o – the expected number of adult parasites produced by a typical adult parasite during its entire period of reproductive maturity; Gatto and De Leo (1998) showed that parasite's competitive ability does not necessarily rank with respect to R o . Finally, Morand and Poulin (2002) did not investigate the range of parasite body sizes that are potentially able to establish in an uninfected host of a given body size at its carrying capacity, nor how this range may shrink in the case the host is already parasitized by one or more competing parasite species.…”
Section: Introductionmentioning
confidence: 99%
“…Population models or reaction-diffusion systems have attracted enormous interest both in the mathematical community and as abstract versions of real biological dynamics [8].Every year, millions of hectares of agricultural land are treated with released Trichogramma wasps [15]; for instance, to protect sugar cane from the sugar cane borer, Chilo spp., in China, or to protect corn fields from the European corn borer, OstrinianubilalisHübner, in Western Europe. Theoretical studies of host-parasitoid interactions go back to Nicholson and Bailey [3,9,13].…”
Section: Introductionmentioning
confidence: 99%